Pendekar (Penderes Badek Karangsari) Program CSR PT Pertamina (Persero) Fuel Terminal Maos - Ardi Maulana Mubarok; Faries Faridan; Faishol Adib T; Della N; Aldita Cindy (Institut Agama Islam Negeri Bengkulu, 2021)
The potential for coconut sugar production in the Karangsari Village Area, Adipala District, Cilacap Regency is quite large. The market potential, both domestic and export, is large enough for coconut sugar production so that tappers need assistance so that their products are ready to be marketed to a wider range. PT.Pertamina (Persero) has a CSR (Corporate Social Responsibility) program which aims to provide sustainable benefits for the community and environmental preservation. Implementation of the CSR program from PT Pertamina (Persero) Fuel Terminal Maos, based on local potential and culture, namely Coconut Sugar Making in Karangsari Village, the name of Pendekar (Penderes Badek Karangsari). Collaborating with several parties, one of which is the Nira Cahaya Sejahtera Cooperative and the Karangsari Village Government. There are several problems faced by the tappers group, namely still using sulfuric chemicals, using firewood to cook sugar and using used PVC paint cans. The solution is Pertamina Fuel Terminal Maos to replace the use of sulfid to use laru, initiate the conversion to gas fuel, namely 12 kg LPG and help replace the paint cans used as pongkor using 2000 food grade pongkor with a capacity of 4 liters per pongkor. The results of the CSR Program PT Pertamina (Persero) Fuel Terminal Maos hopes that Karangsari Village Ants Sugar Products can reach a wider market share, not only domestically but also abroad.